Türk popülasyonunda miyokard infarktüsü riski ile anjiyotensin dönüştürücü enzim insersiyon / delesyon gen polimorfizminin ilişkisi - (:unkn) unknown (My University, 2002)
Amaç: Son zamanlarda yapılan çalışmalarda anjiyotensin konverting enzim (ACE) geninin DD/ID/II polimorfizmi ile kardiyovasküler hastalıklar arasında ilişki olduğu ile ilgili bazı kanıtlar gösterilmiştir. Bu çalışmanın amacı; ACE gen polimorfizmi ile miyokard infarktüsü (Mt) riski arasındaki ilişkiyi daha önce Ml geçirmiş olan hastalarda tespit etmektir. Yöntem: Bu çalışmaya, Vakıf Gureba Hastanesi Koroner Yoğun Bakım Unitesi'nde izlenen hastalar alınmıştır. Toplam 96 hasta çalışmaya alınmıştır (yaş ortalaması: 57.3 ± 10.2). Yaş olarak uygun 39 sağlıklı gönüllü de kontrol grubu (yaş ortalaması. 54.3 ± 9.9) olarak seçilmiştir (p> 0.05 ). ACE genotiplerini ayırmada polimeraz zincir reaksiyonu ve agaroz jel elektroforezi teknikleri kullanılmıştır. Bulgular: Hasta grubunda DD/ID/II genotip sıklığı sırasıyla %33.0, %61.5, %5.2 iken, kontrol grubunda %53-6, %43.6, %2.6'dır. Hasta grubunda ID genotipi de istatistiksel olarak anlamlı düzeyde yüksek oranda bulundu. Allel sıklığı için yapılan analizlerde D alleli %64.1 vel alleli %35.9 olarak bulundu. Kontrol grubunda da D allel sıklığı %75.6,1 allel sıklığı %24.4 idi. Allel sıklığı açısından hasta ve kontrol grupları arasında istatistiksel f ark yoktu (p> 0.05). ACE geninin DD/ID/II polimorfizmi ile koroner risk faktörlerinden yaş, diyabet, hipertansiyon, aile öyküsü, sigara alışkanlığı, düşük HDL, yüksek kolesterol ve sol ventrikül hipertrofisi açısından da fark tespit edilmedi (p> 0.05). Yorum: Sonuç olarak, miyokard infarktüsü geçiren Türk hastalarda ID genotipi sıktır. ACE geninin DD/ID/II polimorfizmi ve koroner risk f aktörleri arasında da korelasyon yoktur ve ACE geninin D allelinin bulunması Türk hasta popülasyonunda Mî riskinde anlamlı artışa neden olmamaktadır.

Objective: Recent studies showed some evidence of relationship between angiotensin converting enzyme (ACE) gene DD/ID/II polymorphism and cardiovascular diseases. The aim of the present study was to investigate the association of ACE gene polymorphism and the risk ofmyocardial infarction in the patients with the history of myocardial infarction. Method; The study was focused on the patients of Vakıf Gureba Hospital Coronary Intensive Unite. Totally 96 patients were included in the study (mean age 57.3 ± 10.2). Age matched 39 healthy volunteers were selected as a control group (mean age 54.3 ± 9.9) (p> 0.05). Polymerase chain reaction and agarouse gel electrophoresis techniques were used to identify the ACE genotypes. Results: The frequency of ACE DD/ID/II genotypes were 33-0%, 61.5%, 5.2% in patients groups and 53-6%, 43-6%, 2.6% in control group respectively. ID genotype was statistically significantly high in patients group (p= 0.05). Additional analyses were assumed for attelé frequency. The frequency of D attelé was 64.1% and I attelé was 35.9% in patients group. In control group the frequencies were 75.6% for D attelé, 24.4% for I attelé. There were no statistically significant differences between control and patient grups in terms of attelé frequency (p> 0.05). There were no correlation between DD/ID/II polymorphism of ACE gene and coronary risk factors such as age, diabetes mellitus, hypertension, family history, smoking habits, low HDL, high cholesterol and left ventricular hypertrophy (p> 0.05). Conclusion: In conclusion, ID genotype is high among the Turkish patients with myocardial infarction history. There was no correlation between ACE gene DD/ID/II polymorphism and coronary risk factors and the presence of D attelé of ACE gene caused no appreciable increase for the risk ofmyocardial infarction in Turkish patient population.
Association of angiotensin converting enzyme polymorphism and the risk of myocardial infarction in Turkish patients
Keywords: Kalp ve Kalp Damar Sistemi; Hematoloji